2012
DOI: 10.1016/j.cognition.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

All words are not created equal: Expectations about word length guide infant statistical learning

Abstract: Infants have been described as ‘statistical learners’ capable of extracting structure (such as words) from patterned input (such as language). Here, we investigated whether prior knowledge influences how infants track transitional probabilities in word segmentation tasks. Are infants biased by prior experience when engaging in sequential statistical learning? In a laboratory simulation of learning across time, we exposed 9- and 10-month-old infants to a list of either bisyllabic or trisyllabic nonsense words, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 40 publications
8
74
0
Order By: Relevance
“…But neither process, alone, is able to account for cue-based statistical learning: the fact that prior experience enables learners to identify phonological regularities and use those regularities to constrain subsequent extraction (e.g., Lew-Williams & Saffran, 2012;Thiessen & Saffran, 2007). By combining the processes of integration and extraction in a single framework, we believe that it is possible to explain cue-based statistical learning.…”
Section: Linking Extraction and Integration Through Attentionmentioning
confidence: 99%
“…But neither process, alone, is able to account for cue-based statistical learning: the fact that prior experience enables learners to identify phonological regularities and use those regularities to constrain subsequent extraction (e.g., Lew-Williams & Saffran, 2012;Thiessen & Saffran, 2007). By combining the processes of integration and extraction in a single framework, we believe that it is possible to explain cue-based statistical learning.…”
Section: Linking Extraction and Integration Through Attentionmentioning
confidence: 99%
“…Recent studies have suggested that the learning of regularities is subject to a primacy effect (Gebhart, Aslin, & Newport, 2009;Jungé, Scholl, & Chun, 2007;Jiang, Swallow, Rosenbaum, & Herzig, 2013;Lew-Williams & Saffran, 2012). For example, in one study (Gebhart et al, 2009) participants were first exposed to one artificial language containing syllables that reliably co-occurred in a specific order.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, preexposure to units of lengths matching the to-be-segmented units contributes to infants' speech segmentation (Lew-Williams & Saffran, 2012). For adults, learning has been reported for irregularlength units (Tyler & Cutler, 2009), but to our knowledge, no adult study has made direct comparisons of AL learning with units of regular or irregular lengths.…”
mentioning
confidence: 95%